Competition and Coordination in Bank Regulation: The Financial Crisis of 2007–09. Issue 7 (6th June 2016) - Provost, Colin
ABSTRACT: The ability of businesses to shift regulatory jurisdictions has long raised questions about whether this generates a regulatory race to the bottom (RTB). Prior to the Financial Crisis of 2007–09, the structure of U.S. federal bank regulation raised similar questions, as banks could choose their regulator and regulators received fees for assessing banks. I investigate this question, through the theoretical lenses of bureaucratic structure, regulatory capture and bureaucratic reputation. Relying on quantitative and qualitative data, I find that the initial regulatory structure did induce a regulatory RTB, but once the Financial Crisis had begun, reputational fears on the part of federal agencies reversed the race, as the regulators strengthened standards and brought more enforcement actions. The paper ultimately shows that multiple theories help to explain what is going on with regulatory RTBs.